Preparation and characterization of plastic wood from cellulosic residues - Fadhil, Iman Nasr; Al-Sarraf, Abdulhameed Raheem (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In this study, crop residues from rice husks were used to enhance the properties of the prepared wood-plastic composites (W.P.C) are made from epoxy (EP) and unsaturated polyester (UPE) at a ratio of (50:50) and reinforced with scales in different proportions, both types are fine (300μm≤) and coarse (300μm>). These blends were undergoing (wear, impact, hardness, differential scanning calorimetry (DSC), and thermal conductivity) tests and the results showed the best weight fraction. is the fine particle weight fraction at 25% and coarse at 15%, depending on the studied tribological characteristics. The results showed by thermal properties of glass transition temperatures (Tg). For each of the (EP,UP, and50:50 blend), and it notices that the thermal conductivity (K) of Ep recorded high values of up to (0.198) W/m.ͦk, while it recorded the lowest thermal conductivity of UP before the blend is (0.17) W/m.ͦk, as for the blend (50-50) the thermal conductivity is (0.19) W/m.ͦk, The thermal conductivity of the blend is slightly lower than that of EP alone.